Refractory tracheoesophageal fistula treated using multi-stage surgery: A case report - Nakagawa, Yoichi; Makita, Satoshi; Uchida, Hiroo; Hinoki, Akinari; Shirota, Chiyoe; Sumida, Wataru; Amano, Hizuru; Okamoto, Masamune; Takimoto, Aitaro; Ogata, Seiya; Takada, Shunya; Kato, Daiki; et al. (Frontiers in Pediatrics, 2022)
A tracheoesophageal fistula (TEF) recurs in approximately 2–13% of cases of esophageal atresia with TEF that are treated surgically. Currently, there is no consensus on the most effective treatment to prevent recurrent TEF (rTEF). Herein, we present a patient with type C esophageal atresia who underwent thoracoscopic esophago-esophageal anastomosis and TEF repair at 2 days old. However, rTEFs were observed at 3, 6, and 11 months old, and thoracoscopic TEF repairs using a pleural patch, fascia lata graft, and pectoralis major myocutaneous (PMMC) flap were performed, respectively. A fourth recurrence led to mediastinitis, shock liver, disseminated intravascular coagulopathy, and a compromised respiratory status. Hence, laparoscopic esophageal transection was first performed to improve the respiratory condition by preventing the regurgitation of gastric contents. Once the patient was stable, a subtotal esophageal resection with TEF closure followed by gastric tube reconstruction was performed. In conclusion, we encountered a case of refractory rTEF that was repaired four times using various techniques, including a fascia lata graft and PMMC flap. However, TEF still recurred after these four operations. The final surgical strategy involved esophageal transection as palliative therapy which improved the respiratory condition, followed by TEF closure and subtotal esophageal resection. Finally, esophageal reconstruction using a gastric tube after the complete remission of inflammation was effective. This multi-stage surgery was considered the only choice to rescue the patient and effectively prevent another recurrence.